The Association of Pediatric Critical Care Medicine Training Programs with Research Publication Productivity and Employment Outcomes of Their Graduates - Basu, Sonali; Horak, Robin; Pollack, Murray M. (Journal of Pediatric Intensive Care, 2020)
Our objective was to associate characteristics of pediatric critical care medicine (PCCM) fellowship training programs with career outcomes of PCCM physicians, including research publication productivity and employment characteristics. This is a descriptive study using publicly available data from 2557 PCCM physicians from the National Provider Index registry. We analyzed data on a systematic sample of 690 PCCM physicians representing 62 fellowship programs. There was substantial diversity in the characteristics of fellowship training programs in terms of fellowship size, intensive care unit (ICU) bed numbers, age of program, location, research rank of affiliated medical school, and academic metrics based on publication productivity of their graduates standardized over time. The clinical and academic attributes of fellowship training programs were associated with publication success and characteristics of their graduates' employment hospital. Programs with greater publication rate per graduate had more ICU beds and were associated with higher ranked medical schools. At the physician level, training program attributes including larger size, older program, and higher academic metrics were associated with graduates with greater publication productivity. There were varied characteristics of current employment hospitals, with graduates from larger, more academic fellowship training programs more likely to work in larger pediatric intensive care units (24 [interquartile range, IQR: 16–35] vs. 19 [IQR: 12–24] beds; p < 0.001), freestanding children's hospitals (52.6 vs. 26.3%; p < 0.001), hospitals with fellowship programs (57.3 vs. 40.3%; p = 0.01), and higher affiliated medical school research ranks (35.5 [IQR: 14–72] vs. 62 [IQR: 32, unranked]; p < 0.001). Large programs with higher academic metrics train physicians with greater publication success (H index 3 [IQR: 1–7] vs. 2 [IQR: 0–6]; p < 0.001) and greater likelihood of working in large academic centers. These associations may guide prospective trainees as they choose training programs that may foster their career values.
Keywords: pediatric intensive care unit; fellowship training; publication productivity